FREQUENCY OF CONVERSION TO OPEN CHOLECYSTECTOMY AMONG MALE AND FEMALE PATIENTS UNDERGOING LAPAROSCOPIC CHOLECYSTECTOMY - Sajid Rehman Randhawa; Ijaz Tanveer; Humaira Zafar et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVES: To determine the frequency of conversion to open cholecystectomy among male and female patients undergoing laparoscopic cholecystectomy. STUDY DESIGN: cross sectional study SETTING: This study was conducted in surgical departments, Allied & DHQ Hospitals Faisalabad. DURATION OF STUDY: 18 months from 01-01-2010 to 30-06-2011 SAMPLE SIZE: 144 patients (72 in each group i.e. male and female) METHODS: Patients between 25 to 60 years of age of either gender with BMI less than 30 subjected to laparoscopic cholecystectomy on elective list. Various parameters (age, sex, duration of surgery, conversion to open cholecystectomy, reason for conversion) were analyzed. RESULTS: Statistical analysis revealed overall mean age 44.79 years and the mean duration was 34.98minutes. Mean age for male patients was 46.29 years and for female patients was 43.29years. Mean duration of laparoscopic cholecystectomy in male patients was 41.54 minutes and in female patients was 28.42 minutes. Conversion to open cholecystectomy in male was 11.1% and in female 2.8%. Main reason for conversion to open cholecystectomy was excessive bleeding 62.5% in male and 100% in female patients. Other reasons for conversion seen in male patient were biliary leakage 25% and adhesions 12.5%. CONCLUSION: Laparoscopic cholecystectomy can be performed safely in male patients with symptomatic gallstones. The duration of surgery, difficulty in surgery and conversion to open surgery is more in male patients as compared to female patients.